Pengaruh Transformasi Digital Pada Produktivitas Dan Profibilitas Perusahaan Kecil dan Menengah (UKM) - Moses Soediro; Adrie Oktavio; Ivana Grasielda; Verina Wijaya; Christy Widyawati (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This study aims to analyze the effect of digital transformation on productivity and profitability of SMEs in the trading sector in Surabaya City. Data were collected through a survey involving 50 SMEs that have adopted digital technology. The results show that the use of digital technologies, including e-commerce, inventory management systems, and online payments, significantly improves the operational efficiency and profitability of SMEs. Most SMEs reported increased sales and profit margins after adopting digital technologies. However, lack of technological know-how and budget constraints are the main challenges in the digital transformation process. Therefore, support from the government and relevant institutions is needed to provide training and financial assistance to encourage wider adoption of digital technologies. This research provides an in-depth insight into the benefits and challenges of digital transformation for SMEs in Surabaya, and provides recommendations to accelerate the adoption of digital technology among SMEs